3D-Printed masks as a new approach for immobilization in radiotherapy - a study of positioning accuracy - Häfner, Matthias; Giesel, Frederik L.; Mattke, Matthias; Rath, Daniel; Kauczor, Hans-Ulrich; Schenk, Jens-Peter; Debus, Jürgen; Sterzing, Florian (OncoTarget, 2018)
Oncotarget | https://doi.org/10.18632/oncotarget.24032 Matthias Felix Haefner, Frederik Lars Giesel, Matthias Mattke, Daniel Rath, Moritz Wade, Jacob Kuypers, Alan Preuss, Hans-Ulrich Kauczor, Jens-Peter Schenk,...
Drei D
Gesehen am 19.08.2019